Driving Personnel Performance: The Role of Leadership, Discipline, and Motivation with Job Satisfaction as a Mediator at Kodim 0802/Ponorogo - Soerjono, Dwi; Supanto, Fajar; Sunardi, Sunardi (Universitas Diponegoro, 2026)
This research seeks to examine how transformational leadership style (TLS), work discipline, and work motivation affect job satisfaction and their subsequent influence on employee performance. This study employed a quantitative method using a causal-associative approach. The population consisted of 548 staff members, with a sample of 232 respondents determined using Slovin’s formula. Data analysis was conducted using the SEM-PLS. The findings suggest that TLS, adherence to work discipline, and motivation at work have a positive and significant impact on both job satisfaction and employee performance. Additionally, job satisfaction significantly affects performance and serves as a mediating factor. In conclusion, improving the quality of leadership, discipline, and motivation can optimally enhance job satisfaction and personnel performance. Therefore, Military District Commanders should strengthen the implementation of transformational leadership, improve the disciplinary system, and develop motivation programs to enhance organizational performance.